Small-Group Interactions with Music and Others in Social Dance - Marchiano, María (2019)
Motivation. In musical environments, large groups of people synchronize on intra-personal, inter-personal, and inter-group levels (Clayton, 2013). Motion behaviour with music has been studied in personal, dyadic (Carlson et al., 2018), and large group’s levels in dance conditions. We aim at studying personal and interpersonal small-group level interactions with music in an electronic dance music (EDM) social context. Methodology. Stimulus: Audiovisual recording of an EDM party in La Plata City, Argentina. Musical analysis: musicological analysis of form. Movement analysis: Observation of a 4:26 minutes of Tech House track, interactive behaviour and microanalysis of legs’ motion patterns of 15 dancers. Results. Small-group interaction: people group together in circles (2-5 people each). Each group shows two kinetic behaviours: (i) a shared 2 beat/4 beat leg’s motion pattern in entrainment with musical metre; and (ii) a dyadic dance-together behaviour inside the small group with momentary inter-personal movement synchronisation, prompted by intentional body contact or mutual gazes. Personal behaviour: most people change their leg’s movement at the main themes’ beginnings (signalled mainly by the salience of the bassline and the high pitched percussions, among others timbral-textural features). Implications. Even though movements’ dancers show a common kinetic behaviour, and a personal, intentional kinetic alignment with musical features such as metric and timbral-textural changes of EDM musical style, interactions within small groups tend to be reduced to dyads, suggesting a transcendence of early traces of communicative musicality in adult social life.